Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 9183 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Cerastium tomentosum L.", "Geometry POLYGON((-30.937499 61.938950,-30.937499 27.059125,52.03125 27.059125,52.03125 61.938950,-30.937499 61.938950))", "HasGeospatialIssue is false", "HasCoordinate is true" ] } The dataset includes 9183 records from 107 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0005474-150615163101818/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences